A molecular phylogeny of Eumorpha (Lepidoptera: Sphingidae) and the evolution of anti‐predator larval eyespots. (20th October 2014) - PONCE, FRANCESCA V.; BREINHOLT, JESSE W.; HOSSIE, THOMAS; BARBER, JESSE R.; JANZEN, DANIEL H.; HALLWACHS, WINNIE; KAWAHARA, AKITO Y.
Abstract Many insects possess conspicuous external circular ring markings that resemble the eye of a vertebrate. These 'eyespots' typically function to startle or otherwise deter predators, but few studies have examined how eyespots have evolved. We study the evolution of the posterior larval eyespot in the charismatic New World hawkmoth genus Eumorpha. While Eumorpha has a range of posterior larval eyespot shapes and sizes, little is known of how this trait has evolved because phylogenetic relationships of Eumorpha remain largely unknown. In this study, we included 62 individuals from 23 of 26 described Eumorpha species, and sequenced four genes (CAD, EF‐1α, Wingless and COI), totaling 3773 base pairs. Maximum likelihood and Bayesian phylogenetic methods produced largely congruent trees with well‐supported relationships. Our analyses reveal that Eumorpha probably had an ancestor with a posterior larval eyespot and that the eyespot was subsequently lost in at least three lineages. Eumorpha appears to have originated in Central and South America and expanded its distribution to North America.